Hospitalized patients' pain experience before and after the introduction of a nurse-based pain management programme: a separate sample pre and post study - Gugsa Nemera Germossa; Ragnhild Hellesø; Ingeborg Strømseng Sjetne (BMC, 2019)
Abstract Background Many patients suffer from unrelieved pain in hospital settings. Nurses have a pivotal role in pain management. Hence, a nurse-based pain management programme may influence how hospitalized patients experience pain. In this study we investigated hospitalized patients' experience of pain before and after the introduction of a two-component nurse-based pain management programme. Methods A quasi-experimental design with a separate sample pretest-posttest approach was conducted on a convenience sample of 845 patients (Survey 1: N = 282; Survey 2: N = 283; Survey 3: N = 280) admitted to the four inpatient units (medical, surgical, maternity, and gynecology) of a university medical center. Data were collected at baseline, before the intervention six weeks after pain management education, and finally immediately after four months of rounding using an interviewer-administered questionnaire adopted from a Brief Pain Inventory and the American Pain Society Patient Outcome Questionnaire. Results All the samples had similar sociocultural backgrounds. The proportion of patients who reported average moderate and severe pain intensity in the last 24 h were 68.8% in Survey 1, 72.8% in Survey 2 and then dropped to 48.53% in Survey 3 whereas those who reported moderate and severe pain intensity at the time of interview were 53.9% in Survey 1, 57.1% in Survey 2 and then dropped to 37.1% in Survey 3. The mean pain interference with the physical and emotional function was generally reduced across the surveys after the introduction of the nurse-based pain management programme. These reductions were statistically significant with p < 0.05. Conclusions Though the survey findings must be taken with caution, they demonstrate that the nurse-based pain management programme positively influenced patient-reported pain intensity and functional interference at the university medical center. This shows the potential clinical importance of the programme for hospitalized patients.